Assessment of Radiation Safety Management System in a Vocational Institution Indonesian Polytechnic of Nuclear Technology X - Gusti Sultan Arifin; Yayi Suryo Prabandari; Marthinus Sutena (Universitas Gadjah Mada, 2025)
Introduction: Occupational safety and health (OSH) are activities to guarantee and protect the safety and health of all workers through efforts to prevent work accidents and work-related diseases. Indonesian regulation concerning the OSH management system state that every company must implement this system in the work area, particularly nuclear facilities, which have a high potential danger level. Objective: The study aims to assesss the efficacy of a radiation safety management system as an effort to protect academic citizens, society, and the environment from the effects of radiation. Methods: This case study used a qualitative descriptive method, including observation, interviews, and document analysis on implementation of radiation safety management requirements in accordance to the prescribed regulations. Result: The result shown that the institute implemented radiation safety management requirements in accordance to the regulations and international guidelines. Conclusions: The radiation safety management system at the institute complies with Indonesian regulations, Indonesia Nuclear Energy Regulatory Agency regulations, and the International Atomic Energy Agency guidelines which require comprehensive evaluation to ensure adequate radiation protection and safety management implementation. Ensuring the everyday radiation culture reduces the risks in disaster situations.